Hubungan Model Problem Based Learning dengan Kemampuan Berfikir Kreatif Mata Pelajaran Sejarah - Indra Teja Lesmana; Syaiful M; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this research is to improve the creative thinking skill of students in historical Subject of grade X Senior High School Teladan in Way Jepara, East Lampung. Descriptive qualitative method was employed for the research design. The subjects of the research were Grade X Senior High School students. The research was conducted into 6 meetings. The research data was obtained by using three times posttests. The result showed that learning history by using Problem Based Learning model can improve students' creative thinking skill, It was seen from data collected. The percentage score of student in posttest 1 was 60%, posttest 2 the percentage increased from 10% into 70% and in posttest 3 percent increased from 17% into 87%. The conclusion of the research showed that there is a positive relationship between Problem Based Learning model and creative thinking skill in historical Subject grade X of Senior High School Teladan Way Jepara, East Lampung.Tujuan penelitian ini untuk meningkatkan kemampuan berfikir kreatif siswa Kelas X SMA Teladan Way Jepara Lampung Timur menggunakan model Problem Based Learning. Desain penelitian kualitatif deskriptif. Subyek penelitian adalah siswa Kelas X SMA. Penelitian dilaksanakan dalam 6 pertemuan. Data penelitian diperoleh dari hasil posttest yang dilakukan sebanyak 3 kali posttest. Hasil penelitian menunjukkan pembelajaran Sejarah menggunakan model pembelajaran Problem Based Learning dapat meningkatkan kemampuan berfikir kreatif siswa, terlihat dari persentase skor siswa yang lulus pada posttest 1 adalah sebesar 60%, pada posttest 2 presentase naik mencapai 10% menjadi 70% dan pada posttest 3 presentase naik mencapai 17% menjadi 87%. Kesimpulan penelitian adalah adanya hubungan positif antara model pembelajaran Problem Based Learning dengan kemampuan berfikir kreatif pada Mata Pelajaran Sejarah siswa Kelas X SMA Teladan Way Jepara Lampung Timur.Kata kunci: berfikir kreatif, hubungan, model problem based learning